2021
DOI: 10.1177/13684310211045794
|View full text |Cite
|
Sign up to set email alerts
|

Claiming solidarity: A multilevel discursive reconstruction of solidarity

Abstract: Solidarity is one of the central concepts in social theory and has gained much attention due to the multiple challenges that the EU has been facing the last decade and due to the most recent COVID-19 pandemic. Although the debate on the nature and conditions of solidarity has been revitalized, there remains a large variety in how to conceptualize solidarity. In contrast to other approaches, we do not conceive solidarity as normative concept, but as descriptive–analytical one. Therefore, we provide a theory-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Previous research has demonstrated that this question is not trivial in political or academic terms: it is politically relevant, because the lack of solidarity in past crises has thrown into doubt the future of the European integration project and the stability of democratic societies (Jones and Matthijs 2017; Lahusen and Grasso 2018). It is also academically crucial, because conceptualizing and measuring solidarity and who is asked to show solidarity with whom is strongly debated in the literature (Baute et al 2019; Kneuer et al 2022). While scholars have extensively studied preferences regarding solidarity in different European countries and across a range of crises (Bechtel et al 2014; Gerhards et al 2020; Katsanidou et al 2022; Lahusen and Grasso 2018), two questions still remain to be addressed.…”
mentioning
confidence: 99%
“…Previous research has demonstrated that this question is not trivial in political or academic terms: it is politically relevant, because the lack of solidarity in past crises has thrown into doubt the future of the European integration project and the stability of democratic societies (Jones and Matthijs 2017; Lahusen and Grasso 2018). It is also academically crucial, because conceptualizing and measuring solidarity and who is asked to show solidarity with whom is strongly debated in the literature (Baute et al 2019; Kneuer et al 2022). While scholars have extensively studied preferences regarding solidarity in different European countries and across a range of crises (Bechtel et al 2014; Gerhards et al 2020; Katsanidou et al 2022; Lahusen and Grasso 2018), two questions still remain to be addressed.…”
mentioning
confidence: 99%